Extração, isolamento e identificação de alcaloide da casca do fruto de Annona crassiflora Mart. e avaliação do seu potencial de inibição da lipase pancreática. - Pereira, Mariana Nunes (2016)
Annonaceae family is an important source of bioactive alkaloids. As part of our ongoing research looking for new bioactive compounds, the ethanol extract from barks of Annona crassiflora fruit was investigated. This extract was subjected to liquid−liquid extration, yielding a bioactive alkaloidal fraction. This fraction was chromatographed using column chromatography followed by HPLC separations. The purified alkaloid was subjected to high-resolution mass spectrometry with electrospray ionization and electron impact, and NMR spectroscopy using 1H, 13C, COSY, HSQC, HMBC and HMBC-N analysis, to afford the stephalagine which belong to aporphine class of alkaloids. The stephalagine was evaluated as pancreatic lipase (PL) inhibitor that was performed by an in vitro kinetic assay using p-nitrophenyl palmitate as substrate. The stephalagine showed inhibitory activity against PL (CC50 8.35 μg.mL–1) and low citotoxicity, thereby suggesting this compound as a potential anti-obesity agent. This study was the first to report the isolation of stephalagine alkaloid from the bark of A. crassiflora fruit.